2001
DOI: 10.1101/gr.157701
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Changes Triggered by Exposure of Haemophilus influenzae to Novobiocin or Ciprofloxacin: Combined Transcription and Translation Analysis

Abstract: The responses of Haemophilus influenzae to DNA gyrase inhibitors were analyzed at the transcriptional and the translational level. High-density microarrays based on the genomic sequence were used to monitor the expression levels of >80% of the genes in this bacterium. In parallel the proteins were analyzed by two-dimensional electrophoresis. DNA gyrase inhibitors of two different functional classes were used. Novobiocin, as a representative of one class, inhibits the ATPase activity of the enzyme, thereby indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
115
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(127 citation statements)
references
References 50 publications
10
115
1
1
Order By: Relevance
“…In a popular approach DNA microarrays are used to generate data on gene expression and to monitor the entire cellular genetic orchestra as a dynamic system (26,49,58). However, a number of experimental and computational studies have suggested that to adequately describe and model cellular metabolism, information on gene expression should be complemented by protein expression data (12,13,19,21). There are numerous cases in which cellular regulation occurs either posttranscriptionally or through posttranslational modifications of proteins.…”
mentioning
confidence: 99%
“…In a popular approach DNA microarrays are used to generate data on gene expression and to monitor the entire cellular genetic orchestra as a dynamic system (26,49,58). However, a number of experimental and computational studies have suggested that to adequately describe and model cellular metabolism, information on gene expression should be complemented by protein expression data (12,13,19,21). There are numerous cases in which cellular regulation occurs either posttranscriptionally or through posttranslational modifications of proteins.…”
mentioning
confidence: 99%
“…inhibit in a mechanistically distinct manner, blocking bacterial DNA replication by binding to the B subunit of bacterial DNA gyrase and inhibiting ATPase activity; 21 this affects DNA supercoiling but does not create double-stranded breaks. 22 Mitomycin C, another natural product, is a classical inducer used in the study of the SOS response, 3 which damages DNA by inducing DNA cross-linking. 23 Although clinically used FQs are synthetic, quinolones occur naturally and a variety of related microbial compounds have been identified with diverse activities such as quorum sensing (Pseudomonas quinolone signal), 24 siderophores (quinolobactin), 25 inhibitors of cytochrome bc 1 complex, 25 etc.…”
Section: Discussionmentioning
confidence: 99%
“…For certain groups of inhibitors it might be beneficial to extend the analysis to different pI ranges or to include different protein fractions to increase the number of marker proteins. For instance, it would be interesting to identify marker proteins in the membrane fraction that help differentiate between membrane-active antibacterial compounds (Apfel et al, 2001;Evers et al, 2001;Gmuender et al, 2001;Gray & Keck, 1999;Singh et al, 2001 According to these patterns, two different serotypes were chosen based on differences in serotypification and antibiotic resistance to proceed to a full proteomic study: the wild boar S. Typhimurium J15(2) strain, which demonstrated resistance to three antimicrobial agents (ampicillin, streptomycin and chloramphenicol) and S. Enteritidis C37(1), recovered from a wild rabbit, where no antibiotic resistance was found. 2-DE ( Figure 5) combined with MS (MALDI-TOF/TOF) and then the correlation with web databases allowed the exact identification and characterization of proteins related to antibiotic resistance, pathogenesis and virulence in both Salmonella strains (Table 2).…”
Section: The Potential Role Of Proteomics In Salmonella Researchmentioning
confidence: 99%
“…Thus, one application of proteomics in drug discovery is the identification of novel antibacterial targets. Some available studies in which proteomics was performed with clear emphasis on antibacterial drug discovery focus on either target validation or mode of action, including those that aim at a better molecular understanding of the mechanisms of action of existing drugs (Apfel et al, 2001;Evers et al, 2001;Gmuender et al, 2001;Gray & Keck, 1999;Singh et al, 2001). In these studies, the proteome of bacteria grown in vitro under standardized conditions in the presence and absence of the antibiotic of interest is analyzed with respect to changes in the protein-expression pattern.…”
Section: Comparative Proteomics and Antibacterial Drug Discovery Processmentioning
confidence: 99%